Implementasi Keselamatan dan Kesehatan Kerja Pada Pekerja Usaha Kecil dan Menengah di Desa Sumber Pasir, Kecamatan Pakis, Kabupaten Malang - Agus Suyetno; Djoko Kustono; Andika Bagus Nur (CV. Multi Kreasi Media, 2023)
Occupational safety and health is very often ignored by small-scale industry players, either because (1) lack of knowledge about the causes of work accidents and (2) because of limited capital to obtain adequate work safety facilities. They think that these two things are problems that cannot be solved. To anticipate this incident, it is necessary to make efforts to prevent work accidents that can overcome the two problems mentioned above. Implementation of the theory of Occupational Safety and Health to prevent accidents at work is the best solution. The formulation of the problem: (1) is there a change in safety behavior towards workers after Occupational Safety and Health training (2) is there a change in K3 knowledge of workers after Occupational Safety and Health training, (3) Is there an effect of age on safe behavior towards workers after training Occupational Safety and Health (4) Is there an effect of age on the knowledge of K3 for workers after the Occupational Health and Safety training? The research method is Quasi Experimental. The number of samples is 31 workers. The results of the study were that there was no change in safety behavior towards workers after Occupational Safety and Health training, (2) There was a change in K3 knowledge of workers after Occupational Safety and Health training (3) There was no effect of age on safe behavior towards workers after Occupational Safety and Health training. and (4) There is an effect of age on the knowledge of K3 for workers after the Occupational Health and Safety training. Suggestion: it is necessary to do more research with a longer time.